MANAGEMENT OF VILLAGE FUNDS TO REMIND THE WELFARE OF THE FARMING COMMUNITY IN NAGERI VILLAGE, JUHAR DISTRICT, KARO REGENCY - hasanah, uswatun; Annisa Ilmi Faried; Siska Monika (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research was conducted in Nageri Village, Juhar District, Karo Regency. This research is motivated by Village Fund Management to Improve Community Welfare. This study used quantitative and qualitative data and the model used was Path Analysis then the sample used amounted to 110 households of data collected by distributing questionnaires. This study was conducted to determine the direct, indirect and total influence between variables, the variables used include Village Apparatus (X1), Community Participation (X2), Village Fund (X3), Agricultural Infrastructure (Y1), Agricultural Distribution (Y2), and Agricultural Community welfare (Z).